x 2 − x y + y 2 x 2 y + x y 2 = 7 = − 2
Solve the above system of equations in the set of real numbers. Then, give your answer as the sum of the solution coordinates. That is:
If the system has the solutions ( x 1 , y 1 ) , ( x 2 , y 2 ) , ( x 3 , y 3 ) , … , then determine x 1 + y 1 + x 2 + y 2 + x 3 + y 3 + … .
Give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! Argh that I didn't see that coming! XD
Log in to reply
Thanks! After comparing our solutions, however, I see that you have six solutions to my three, since you have two solutions ( x , y ) corresponding to each of the three possible values for x + y . My solution doesn't account for this multiplicity, so I'm wondering if it may be incomplete.
Edit: O.k., I see how to get the multiplicity. Each value of x + y corresponds to two solutions, namely ( a , b ) and ( b , a ) .
Log in to reply
No, your solution IS rigorous and complete! x + y goes very well if you have symmetric solutions as I already found. :)
Log in to reply
@Michael Huang – O.k., great, thanks for the confirmation. I added an edit to my previous comment to indicate how our solutions match up. :)
How did you factor that long polynomial?
Log in to reply
Because the expression can be expressed in terms of x 2 + 2 x y + y 2 , we can include extra x y term in the equation.
I noted quickly that x + y = 1 was one solution and then factored that out of the cubic.
let a = x + y , b = x y ⟹ a 2 = 7 − 3 b ⟹ a b = − 2 ⟹ a = − 2 / b 4 / b 2 = 7 − 3 b 4 = 7 b 2 − 3 b 3 3 b 3 − 7 b 2 + 4 = 0 ( b − 1 ) ( 3 b 2 − 4 b − 4 ) = 0 ( b − 1 ) ( 3 b + 2 ) ( b − 2 ) = 0 ⟹ b = 1 , b = − 2 / 3 , b = 2 ⟹ a = − 2 , a = 3 , a = − 1
we just need to solve for the sum of a's and hence, we will arrive to the answer 0 .
Problem Loading...
Note Loading...
Set Loading...
The first of the given equations can be rewritten as ( x + y ) 2 − 3 x y = 7 , and the second as
x y ( x + y ) = − 2 ⟹ x y = − x + y 2 , (as clearly x + y = 0 ). Combining these results gives us
( x + y ) 2 + x + y 6 = 7 ⟹ ( x + y ) 3 − 7 ( x + y ) + 6 = 0
⟹ ( ( x + y ) − 1 ) ( ( x + y ) − 2 ) ( ( x + y ) + 3 ) .
Thus the three possible values for x + y are 1 , 2 and − 3 , which sum to 0 .
Edit: Note that, by symmetry, each of the possible values for x + y corresponds to two solutions ( a , b ) and ( b , a ) , so the complete sum of x k + y k is 1 + 1 + 2 + 2 + ( − 3 ) + ( − 3 ) = 0 .